Growth and Productivity of Silkworm Bombyx mori L. (Lepidoptera: Bombicidae) Given Mulberry (Morus sp.) It Contains Vitamin B1 - Masitta Tanjung (Talenta Publisher, 2021)
The effect of mulberry leaves that contain vitamin B1on the growth and productivity of silkworms (Bombyx mori L.) was studied. This research used Completely Randomized Design (CRD) with the treatments were 10 silkworm feed with an untreated control leaves and an addition 0.1, 0.2, 0.3 and 0.4 mg/100ml of vitamin B1. Every treatment consisted of 3 replications. The results showed that an addition of vitamin B1 inhibited the growth, morphological structure of instars III, and IV such as head length, head diameter, body length, and body diameter, the weight of instars III, V, and the percentage of cocoon shell. Vitamin B1 has no effect on the morphological structures of instars V, the weight of instars IV, the pupae weight, the fiber length, the fiber percentage, the cocoon weight, and the cocoon shell weight. However, the frontal and posterior glands were decreased at the concentration 0.4 mg/100ml